Peripheral airways type 2 inflammation, neutrophilia and microbial dysbiosis in severe asthma. Issue 7 (26th January 2021) - Azim, Adnan; Green, Ben; Lau, Laurie; Rupani, Hitasha; Jayasekera, Nivenka; Bruce, Kenneth; Howarth, Peter
Abstract: Background: IL‐13 is considered an archetypal T2 cytokine central to the clinical disease expression of asthma. The IL‐13 response genes, which are upregulated in central airway bronchial epithelial of asthma patients, can be normalized by high‐dose inhaled steroid therapy in severe asthma. However, this is not the case within the peripheral airways. We have sought to further understand IL‐13 in the peripheral airways in severe asthma through bronchoalveolar analysis. Methods: Bronchoalveolar lavage samples were collected from 203 asthmatic and healthy volunteers, including 78 with severe asthma. Inflammatory mediators were measured using a multiple cytokine immunoassay platform. This analysis was replicated in a further 59 volunteers, in whom 16S rRNA analysis of BAL samples was undertaken by terminal restriction fragment length polymorphism. Results: Severe asthma patients with high BAL IL‐13, despite treatment with high‐dose inhaled corticosteroids, had more severe lung function and significantly higher BAL neutrophil percentages, but not BAL eosinophils than those with normal BAL‐13 concentrations. This finding was replicated in the second cohort, which further associated BAL IL‐13 and neutrophilia with a greater abundance of potentially pathogenic bacteria in the peripheral airways. Conclusion: Our findings demonstrate a steroid unresponsive source of IL‐13 that is associated with BAL neutrophilia and bacterial dysbiosis in severe asthma. Our findings highlight the biological complexity of severe asthma and the importance of a greater understanding of the innate and adaptive immune responses in the peripheral airways in this disease. Abstract : In this study, we stratified biologic naïve severe asthma patients treated with high‐dose inhaled corticosteroid therapy by their bronchoalveolar lavage IL‐13. Patients with high bronchoalveolar lavage IL‐13, despite steroid therapy, have a higher percentage of bronchoalveolar lavage neutrophils. We replicated these findings in a second smaller cohort, which also associated high bronchoalveolar lavage IL‐13 with bacterial dysbiosis. Abbreviations: BAL, bronchoalveolar lavage; ICS, inhaled corticosteroids; OCS, oral corticosteroids.